2022
DOI: 10.1017/s0954579422000724
|View full text |Cite
|
Sign up to set email alerts
|

Examining protective factors for substance use problems and self-harm behavior during adolescence: A longitudinal co-twin control study

Abstract: Sports participation, physical activity, and friendship quality are theorized to have protective effects on the developmental emergence of substance use and self-harm behavior in adolescence, but existing research has been mixed. This ambiguity could reflect, in part, the potential for confounding of observed associations by genetic and environmental factors, which previous research has been unable to rigorously rule out. We used data from the prospective, population-based Child and Adolescent Twin Study in Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…For adolescents, any level of SU is risky and can result in negative developmental outcomes, including disruption of brain development, educational underachievement, behavioral consequences (e.g., driving, sexual behavior), and injury, as well as the potential for inducing or exacerbating mental comorbidities and progression to SUD [6,51]. Furthermore, early-onset substance use is associated with increased psychosocial problems and problematic substance use later in life [52].…”
Section: Transitional Age Youth (Tay)mentioning
confidence: 99%
See 3 more Smart Citations
“…For adolescents, any level of SU is risky and can result in negative developmental outcomes, including disruption of brain development, educational underachievement, behavioral consequences (e.g., driving, sexual behavior), and injury, as well as the potential for inducing or exacerbating mental comorbidities and progression to SUD [6,51]. Furthermore, early-onset substance use is associated with increased psychosocial problems and problematic substance use later in life [52].…”
Section: Transitional Age Youth (Tay)mentioning
confidence: 99%
“…Peer interactions are often enmeshed within physical activities in adolescence, and physical activity is broadly (positively) related to mental health via psychosocial, behavioral, and physiological mechanisms [52]. Two studies that examined pairs of discordant twins on physical activity found that physical inactivity in adolescence was associated with increased consumption of alcohol, drugs, and smoking in young adulthood [52].…”
Section: Physical Activity and Peer Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a systematic review focusing on self-harm and cyberbullying noted that only one third of articles investigated protective factors (Dorol-Beauroy-Eustache and Mishara, 2021). Those reviewed found that life satisfaction, family and school satisfaction protected against self-harm (Dorol-Beauroy-Eustache and Mishara, 2021; Janiri et al , 2021), as did positive peer relationships (Neufeld et al , 2015; O’Reilly et al , 2022). Evidently, further investigation of protective factors in this area is warranted.…”
Section: Introductionmentioning
confidence: 99%